GENERAL PHYSICAL GEOGRAPHIC DESCRIPTION OF THE GEOLOGIC AND OROGRAPHIC STRUCTURE OF KATTAKURGAN REGION (Scientific journal of the Fergana State University, 2024)
The purpose of the study is to analyze the orographic and geological structure of Kattakurgan district. Several methods such as work with literature and stock materials, cartographic, field studies, GIS-technologies were used in the fulfillment of this research work. In the literature and analytical part of the research work, the level of study of natural conditions of Kattakurgan district was considered in detail. Then the geographical position of the district, geological and orographic structure of the earth's surface were analyzed. The geological history of the territory of Kattakurgan district, the processes of mountain formation and modern orographic structures formed as a result of these folds (Aktau and Zirabulok mountains, Kattakurgan depression) were studied. Besides, geological formations and complexes were formed on the territory of the district, epochs (periods) of their appearance, thickness of layers of formations and complexes, what rocks they are composed of, as well as parts of the district where these sediments are located. found were analyzed. As a result of the research it was concluded that the territory of Kattakurgan district consists of a variety of rocks, among which can be found from ancient rocks to modern sediments. Based on the data obtained, a geologic map of Kattakurgan district was created using ArcGIS 10.8 software program.